Optimalisasi Pendidikan Pengelolaan Sampah Untuk Mewujudkan Indonesia Berkemajuan yang Bersih dan Berkelanjutan - Ramadhani, Muhammad Rizqy Zia; Apriliana, Kalista Putri; Khairunnisya, Wandira; Novia, Epriyaloka Anggun Putri Eka; Nadhif, Maura Arthamevia Qorrineta; Azmi, Ulul; Maajid, Muhammad Luthfi Abdul; Fitriyah, Nur Salsa Bela; Atmojo, Hanung Arjuni; Widagdo, Muhammad Daffa Manggala Putra; Wibowo, Sigit Arie (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The main problem faced by the community in Padukuhan Trisigan II, Murtigading Village, is the low awareness and skills in managing waste, especially plastic waste that can pollute the environment. Therefore, the Community Service Program of the University of Muhammadiyah Yogyakarta (PKM UMY) is implemented to increase community understanding and participation in more effective and sustainable waste management. The methods used in this program include socialization, training, and supporting infrastructure by involving various elements of society, including Community Groups (POKMAS), elementary school students, and local community leaders. The main activities include socialization of waste management, Ecobrick Youth assistance for elementary school students, training on making Eco Paving Blocks as a solution for plastic waste and healthy walking activities to increase public awareness of the importance of a healthy lifestyle. The results of this program showed that 85% of the socialization participants stated that they gained a new understanding of better waste management, while 80% of students who participated in the Ecobrick Youth assistance were able to understand and practice making Ecobricks well. In addition, around 95% of Eco Paving Block trainees expressed interest in developing this innovation in their environment. The healthy walk activity also raised public awareness of the importance of regular exercise, with more than 300 residents from various age groups participating. This program proves that an education-based approach and action can increase community awareness and skills in managing waste responsibly and sustainably. The results of this program can be the first step in creating a cleaner, healthier, and sustainability-oriented environment. With this program, the community is expected to continue to develop waste management innovations independently and make them part of daily life to create a greener and more sustainable environment.